Fluoxetine increases plasticity and modulates the proteomic profile in the adult mouse visual cortex - Ruiz-Perera, L. (Sci Rep, 2015)
The scarce functional recovery of the adult CNS following injuries or diseases is largely due to its reduced potential for plasticity, the ability to reorganize neural connections as a function of experience. Recently, some new strategies restoring high levels of plasticity in the adult brain have been identified, especially in the paradigmatic model of the visual system. A chronic treatment with the anti-depressant fluoxetine reinstates plasticity in the adult rat primary visual cortex, inducing recovery of vision in amblyopic animals. The molecular mechanisms underlying this effect remain largely unknown. Here, we explored fluoxetine effects on mouse visual cortical plasticity, and exploited a proteomic approach to identify possible candidates mediating the outcome of the antidepressant treatment on adult cortical plasticity. We showed that fluoxetine restores ocular dominance plasticity in the adult mouse visual cortex, and identified 31 differentially expressed protein spots in fluoxetine-treated animals vs. controls. MALDITOF/TOF mass spectrometry identification followed by bioinformatics analysis revealed that these proteins are involved in the control of cytoskeleton organization, endocytosis, molecular transport, intracellular signaling, redox cellular state, metabolism and protein degradation. Altogether, these results indicate a complex effect of fluoxetine on neuronal signaling mechanisms potentially involved in restoring plasticity in the adult brain.